Attenuation of A(H7N9) influenza virus infection in mice exposed to cigarette smoke - Fukuyama, Satoshi; Shoemaker, Jason E.; Zhao, Dongming; Nagajima, Noriko; Tomita, Yuriko; Maemura, Tadashi; da Silva Lopes, Tiago Jose; Watanabe, Tokiko; Yamayoshi, Seiya; Hasegawa, Hideki; Kawaoka, Yoshihiro (Npj viruses, 2024)
Influenza A(H7N9) virus showed high pathogenicity in humans when it emerged in 2013. Cigarette smoke (CS) causes pulmonary diseases including bronchitis, emphysema, and lung cancer. Although habitual smoking is thought to increase the risk of severe seasonal influenza virus infection, its effect on A(H7N9) virus infection is poorly understood. Here, we employed a mouse model of long-term exposure to CS to investigate the effect of CS on the pathogenicity of A(H7N9) virus infection. Unexpectedly, body weight loss for mice exposed to CS was milder than that for mock-treated mice upon A(H7N9) virus infection. CS exposure improved the survival rate of A(H7N9) virus-infected mice even though virus titers and pathological changes in the lungs were not significantly different between CS-exposed and control mice. Microarray analysis showed that CS-exposure activates cytokine/chemokine activity, immune response, and cell cycle activities that resemble reactivities against A(H7N9) virus infection. Therefore, under conditions where cytokine and chemokine expression in the lungs is already high due to CS exposure, the enhanced expression of cytokines and chemokines caused by A(H7N9) virus infection might be less harmful to the organs compared to the rapid increase in cytokine and chemokine expression in the air-exposed mice due to the infection. CS may thus induce immunoregulatory effects that attenuate severe pulmonary disease during A(H7N9) virus infection. However, these findings do not support CS exposure due to its many other proven negative health effects.